Stereotactic body radiotherapy with CyberKnife® System for low- and intermediate-risk prostate cancer: clinical outcomes and toxicities of CyPro Trial - Borzillo, Valentina; Scipilliti, Esmeralda; Pezzulla, Donato; Serra, Marcello; Ametrano, Gianluca; Quarto, Giuseppe; Perdonà, Sisto; Rossetti, Sabrina; Pignata, Sandro; Crispo, Anna; Di Gennaro, Piergiacomo; D’Alesio, Valentina; et al. (Frontiers in Oncology, 2023)
Simple summary Stereotactic body radiotherapy (SBRT) of 35–36.25 Gy in five fractions with the CyberKnife System yields excellent control with low toxicity in low–intermediate-risk prostate cancer patients. We found no differences in biochemical control and overall survival in relation to dose. There were no significant differences in toxicity or quality of life between the two groups. Aims Stereotactic body radiotherapy (SBRT) is an emerging therapeutic approach for low- and intermediate-risk prostate cancer. We present retrospective data on biochemical control, toxicity, and quality of life of CyPro Trial. Materials and methods A total of 122 patients with low- and intermediate-risk prostate cancer were treated with the CyberKnife System at a dose of 35 Gy or 36.25 Gy in five fractions. Biochemical failure (BF)/biochemical disease-free survival (bDFS) was defined using the Phoenix method (nadir + 2 ng/ml). Acute/late rectal and urinary toxicities were assessed by the Radiation Therapy Oncology Group (RTOG) toxicity scale. Quality of life (QoL) was assessed by the European Organisation for Research and Treatment of Cancer (EORTC) QLQ C30 and PR25. International Erectile Function Index-5 (IIEF5) and International Prostate Symptom Score (IPSS) questionnaires were administered at baseline, every 3 months after treatment during the first years, and then at 24 months and 36 months. Results The 1-, 2-, and 5-year DFS rates were 92.9%, 92.9%, and 92.3%, respectively, while the 1-, 2-, and 5-year bDFS rates were 100%, 100%, and 95.7%, respectively. With regard to risk groups or doses, no statistically significant differences were found in terms of DFS or bDFS. Grade 2 urinary toxicity was acute in 10% and delayed in 2% of patients. No Grade 3 acute and late urinary toxicity was observed. Grade 2 rectal toxicity was acute in 8% and late in 1% of patients. No Grade 3–4 acute and late rectal toxicity was observed. Grade 2 acute toxicity appeared higher in the high-dose group (20% in the 36.25-Gy group versus 3% in the 35-Gy group) but was not statistically significant. Conclusion Our study confirms that SBRT of 35–36.25 Gy in five fractions with the CyberKnife System produces excellent control with low toxicity in patients with low–intermediate-risk prostate cancer. We found no dose-related differences in biochemical control and overall survival. Further confirmation of these results is awaited through the prospective phase of this study, which is still ongoing.